Analisis Perhitungan Harga Pokok Produksi Dengan Menggunakan Metode Full Costing Sebagai Dasar Perhitungan Harga Jual (Studi Kasus Pada Kertinaâ€™s Home Industry) - Pelealu, Axel J. H.; Manoppo, Wilfried S.; Mangindaan, Joanne V. (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
The calculation of cost of goods manufactured is important to consider in determining the price of a product. The purpose of this study is to determine whether there is a comparison between the calculation of the cost of production according to the company compared to the full costing method and the determination of the selling price according to company calculation compared with cost plus pricing method. The type of research used is descriptive quantitative research type, and research approach used is comparative approach. From the results of data analysis shows that the calculation of the cost of production of the company is lower than the calculation of cost of production by using the method of full costing. The difference from the calculation of cost of production according to the company compared with the full costing method that is Rp. 10.133. This is because in the calculation of factory overhead costs, the company does not take into account some costs into the cost of production such as maintenance and maintenance costs of production equipment, and the cost of depreciation of production equipment. Â In addition, the sale price of the product with a mark-up rate of 40% according to the company and cost plus pricing method has a difference of Rp. 2,083. This is because the company in determining the selling price of its products does not take into account non-production costs, and companies do not use the full costing method in determining the cost of production.